Is AI Effective in Pediatric Care? A Professional Analysis of Benefits and Challenges - Rasit, Dinc (Rasit Dinc Digital Health & AI Research, 2024)
The integration of Artificial Intelligence AI into healthcare is rapidly transforming clinical practice, but its application in pediatric care presents a uni...
Keywords: Digital Health; Diagnostics; Artificial Intelligence; Healthcare Innovation; Precision Medicine